KAJIAN PEWARISAN PENGETAHUAN ETNOBOTANI PADA ANAK-ANAK KAMPUNG ADAT BADUY - Musafak, Moch. Ali (2015)
This study aims to determine the inheritance of children's ethnobotany knowledge of ethnobotany in children Indigenous Baduy village and to know ethnobotany knowledge possessed children Indigenous Baduy village. The method used in this research is descriptive qualitative. Subjects in this study were children of Indigenous Baduy village who have aged between 7-15 years old and their parents. Data obtained from semi-structured interviews, direct observation and documentation during the study. Data from the survey results revealed that the inheritance of knowledge is done vertically through learning dialukan by parents to their children and are harizontal through dialkukan learning with children who have the same age. Children of Indigenous Village Inner Baduy have knowledge of ethnobotany higher with an average value of 42% and Children's of Indigenous Village Outer Baduy average value of 24%. Factors affecting children's knowledge of ethnobotany Indigenous Baduy village dwellings and daily activities.